PELATIHAN DESAIN MENU MAKANAN UNTUK POKDARWIS DALAM RANGKA MENDUKUNG PENGEMBANGAN DESA WISATA DI DESA SUKAJADI, BOGOR - Riana Dwi Putri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Programs to increase the interest of local and international tourists to villages tourism need to be supported by knowledge of human resources in the tourism industry, especially regarding designing food and beverage menus, which are one of the supporters in tourism products. The purpose of this community service activity (PKM) is to provide training to help tourism awareness groups (Pokdarwis) in Sukajadi Village, Tamansari District, Bogor. Based on interviews conducted before the program started, the people of Sukajadi Village as a whole did not know how to design food and drink menus and how to promote regional specialties from Sukajadi Village, so training was carried out on the basic knowledge that Pokdarwis should have on how to design food and drink menus. Through discussions during training with Pokdarwis, creative ideas regarding menus have the potential to be developed. Participants in this training can understand well all the material provided. Participants also realized the importance of deepening their knowledge of designing food and beverage menus to produce superior tourism products.